A mutated recombinant subunit vaccine protects mice and guinea pigs against botulinum type A intoxication. Issue 2 (1st February 2018) - Yu, Chi Ho; Song, Dong Hyun; Choi, Jun Young; Joe, Hae Eun; Jeong, Woo Hyeon; Hur, Gyeung Haeng; Shin, Young Kee; Jeong, Seong Tae
ABSTRACT: Botulinum neurotoxins (BoNTs) are the most potent toxins to mammals. A toxoid vaccine was previously used for prevention of botulinum intoxication; however, this vaccine is no longer available. Currently, no approved botulinum vaccines are available from the Food and Drug Administration (FDA). Recently, a recombinant host cell receptor-binding subunit created for use as a potential vaccine completed phase 2 clinical trials. The current study designed a vaccine candidate against BoNT type A (BoNT/A) using a structural design. Our vaccine candidate was the BoNT/A heavy chain C-terminal region (HCR) that contained the point mutation BA15 (R1269A) within the ganglioside-binding site. A Biacore affinity test showed that the affinity of BA15 for ganglioside GT1b was 100 times lower than that of the HCR. A SNAP25 cleavage assay revealed that immunized sera blocked SNAP25 cleavage of the BoNT/A toxin via BA15. In an in vivo experiment, mice and guinea pigs immunized with BA15 produced neutralizing antibodies that protected against 3, 000 LD50 of BoNT/A. In conclusion, the results of both in vitro and in vivo assays showed that our BA15 vaccine candidate was similar to the recombinant host cell receptor-binding subunit vaccine. The inability of BA15to bind ganglioside shows that BA15 is a potential safe vaccine candidate.